Catalogue of Egyptian, Near Eastern, Greek and Roman Antiquities, African, Oceanic, American and Indian Art. The Property of the late M. Ferdinand Michel and other owners. Sotheby Sales Catalogue (1965)
Day of sale: Jan. 25, 1965; Vorderasiatische Altertümer, p. 21-24 = nos. 92-106; u.a. Beycesultan?